2012
DOI: 10.4236/ijoc.2012.24054
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Tyrosinase Activity from Olea Leaf Extract Depended on Seasonal Variations and Chromagraphy Treatment

Abstract: In the present study, olive leaf extract, harvested from four seasons, extracted with solvent (methanol and water), was treated by D101 and Sephadex LH-20, and divided into 10 fractions by TLC detection. The antioxidant activity was evaluated using DPPH, superoxide anion scavenging and reducing power assays. Tyrosinase inhibitory activity was also performed with L-DOPA as substrate. On extraction method, there is no significant difference in methanol and water. Among 12 months, autumn showed the best harvest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
2
3
1
Order By: Relevance
“…Comparing data for AOA the highest values were observed for cultivar Chondrolia Halkidiki grown in vitro and in vivo. Presented results are in accordance with Yang and Ouyang (2012) and Lafka et al (2013) confirming the highest antioxidant potential of olive leaf extracts. Present investigation demonstrated that in vitro plants possess higher content of TPC and AOA in comparison with in vivo cultivated olive plants.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing data for AOA the highest values were observed for cultivar Chondrolia Halkidiki grown in vitro and in vivo. Presented results are in accordance with Yang and Ouyang (2012) and Lafka et al (2013) confirming the highest antioxidant potential of olive leaf extracts. Present investigation demonstrated that in vitro plants possess higher content of TPC and AOA in comparison with in vivo cultivated olive plants.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies have shown that compounds, derivatives from the leaves and fruits of the olive tree are strong antioxidants (Kontogianni and Gerothanassis, 2012). For the leaf extracts is proved antimalarial, anti-HIV action, vasomotor and hypoglycemic effects (Yang and Ouyang, 2012;Lafka et al, 2013). Many reports indicate that olive leaves contain significant amounts of oleuropein and phenols possessing high antioxidant capacity (Mourtzinos et al, 2007;Lee et al, 2009;Abaza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic data analysis using Lineweaver-Burk plot, which is also called the double reciprocal plot reveals that the inhibitory mechanism of both methanol leaf extracts on mushroom tyrosinase was competitive, viz partial competitive inhibition. This correlates with Yang and Quyang [19] conclusion for Olea leaf extract analysed by Lineweaver-Burk plot. Furthermore, L. esculentum var.…”
Section: Discussionsupporting
confidence: 87%
“…This implies that methanol leaf extract of Eva F1 variety has a higher affinity for the active site of mushroom tyrosinase than that of Hausa variety. Also, the K I value obtained in this study is considerably lower than that obtained by Yang and Quyang [19] for Olea europa leaf extract, which had a K I value of 0.226 mg/mL.…”
Section: Discussioncontrasting
confidence: 87%
“…The activity of mushroom Tyr was measured following the method described earlier by Yang and Ouyang. 21 The conditions of the enzymatic crosslinking reactions were decided based on a previous study 22 and pre-experiments. Figure 1(A) displays the reaction formula showing the crosslinking reaction.…”
Section: Crosslinking Of Fish Pv By Tyr In the Presence Of Camentioning
confidence: 99%